L'apprentissage hybride en sciences de gestion : ce qu'en pensent les étudiants - Jean-Pierre Béchard; Catherine Carré; Gabriella Frankel; Zoffirath Dissou; Céline Bazinet; Gilles Cazabon; Yves Goyette
Dealing with an increasingly competitive environment, business schools and faculties are more and more engaged in hybrid learning approaches. This is why our institution designed and implemented a blended-learning project during the years 2009 to 2011 in ten distinct courses for a total of 27 groups. We gathered the perceptions of 805 students in order to better understand their reasons for enrolling in such a course, their level of satisfaction with the teaching and learning environment and their views regarding the impacts on learning. All the results coming from a questionnaire were analyzed in view of evaluating pedagogical innovation and its potential for institutionalization. The article ends with four proposals grounded in a theoretical framework on hybrid learning and teaching.